Is It Necessary to Drain the Kidney with Gestational Pyelonephritis? - S. V. Shkodkin (Вестник урологии, 2020)
Summary. Pyelonephritis during pregnancy is considered as a complicated urinary tract infection. Many Russian publications recommend drainage of the upper urinary tract in pregnant women with pyelonephritis.Purpose of the study. To evaluate the effectiveness and safety of drainage-free management of patients with pregnant pyelonephritis, as well as the epidemic prevalence of pyelonephritis during pregnancy.Materials and methods. The efficacy of conservative therapy and postural drainage in 162 pregnant women with pyelonephritis over the past 3 years has been retrospectively evaluated.Results. The highest frequency of pyelonephritis during pregnancy was noted in the second trimester. Conservative therapy was effective in most patients. Ureteric stent drainage was performed in 3.7% of patients. Hospitalization period increased in this group reliably.Conclusions. Pyelonephritis during pregnancy cannot be considered obstructive. Drainage-free management of pregnant women with pyelonephritis should be considered as a priority approach.